Assessment of neuropsychiatric indicators in children and adolescents with primary brain tumors and other brain space occupying lesions before and after surgery - Nasehi, Samira; malek, Ayyoub; Meshkini, Ali; Shafiee-Kandjani, Ali Reza; Amiri, Shahrokh; Salehpoor, Firooz; Mirzaei, Farhad; Shahrokhi, Hasan; Dastgiri, Saeed; Farhang, Sara (Iranian Journal of Child Neurology, 2022)
Objective Cognitive abilities may be impaired due to brain lesions in children and adolescents. This study aimed to investigate neuropsychiatric indicators in children and adolescents with primary brain tumor and other brain space occupying lesions (SOL) before and after surgical procedure. Methods & materials the current study is a pre and post study which was conducted on 81 patients with brain space occupying lesions aged less than 18. Patients with metastatic brain tumors were excluded. The study was performed between 20 December 2016 to 20 December 2017 on patients hospitalized in neurosurgery ward of Imam Reza university hospital, Tabriz, Iran. Before and after surgical procedure, Digit span forward and backward Task (to assess working memory), Stroop task and Trail Making Task A & B (to assess attention) and Rey Osterrieth Complex Figure Test (to assess Visual Spatial Memory) were done. Then, scores of tests were compared with normal values as well as the post-surgery scores. Results the most prevalent type of space occupying brain lesion was medulloblastoma and the most common region of involvement was posterior fossa tumor. Scores of all tests after surgery comparing to before surgery were significantly improved (P<0.05). In assessment of Digit span forward and backward Task with standard scores, there was no significant difference among scores of patients before surgery with the standard value (P>0.05). Regarding scores of various stages of Rey Osterrieth Complex Figure Test, the scores of immediate recall stage was significantly low (P<0.05). Among Trail Making Task A & B and stroop task, before surgery, just the Trail Making Task A & B was significantly increased (P<0.05). Scores of Trail Making Task A was significantly higher in patients with medulloblastoma and anatomically in left temporal tumors which indicate greater damage of attention field (P<0.05). In addition, in cerebellar tumor, scores of immediate recall stage of Rey Osterrieth Complex Figure Test was significantly lower (P<0.05). Conclusions Visuo-Spatial Memory and attention in pre-surgery assessments was significantly impaired comparing to general population (P<0.05). Working memory, Visuo-Spatial Memory and attention showed improvement comparing to pre-surgery. Deficits in attention domain was greater in medulloblastoma.